GROWTH PATTERNS OF LEGUME PLANTS UNDER VARIED LEVELS OF DROUGHT STRESS TREATMENT - Veronica Wahyuni (American Journal Of Agriculture And Horticulture Innovations, 2024)
This study investigates the growth patterns of legume plants under different levels of drought stress treatment. Legume plants are crucial components of agricultural ecosystems, providing essential nutrients and contributing to soil fertility. However, their growth and productivity can be severely impacted by drought stress, which is becoming increasingly prevalent due to climate change. In this research, legume plants are subjected to various levels of drought stress treatment, and their growth parameters such as biomass accumulation, leaf area, and physiological responses are measured and analyzed. The findings contribute to our understanding of how legume plants respond to drought stress and provide insights into potential strategies for mitigating the adverse effects of drought on legume crop production.